Amphiphilic gold nanoparticles perturb phase separation in multidomain lipid membranes. Issue 38 (23rd September 2020) - Canepa, Ester; Salassi, Sebastian; de Marco, Anna Lucia; Lambruschini, Chiara; Odino, Davide; Bochicchio, Davide; Canepa, Fabio; Canale, Claudio; Dante, Silvia; Brescia, Rosaria; Stellacci, Francesco; Rossi, Giulia; et al.
Abstract : Experiments and simulations reveal that amphiphilic nanoparticles suppress phase separation in neuronal-like lipid bilayers and form bilayer-embedded ordered aggregates. Abstract : Amphiphilic gold nanoparticles with diameters in the 2–4 nm range are promising as theranostic agents thanks to their spontaneous translocation through cell membranes. This study addresses the effects that these nanoparticles may have on a distinct feature of plasma membranes: lipid lateral phase separation. Atomic force microscopy, quartz crystal microbalance, and molecular dynamics are combined to study the interaction between model neuronal membranes, which spontaneously form ordered and disordered lipid domains, and amphiphilic gold nanoparticles having negatively charged surface functionalization. Nanoparticles are found to interact with the bilayer and form bilayer-embedded ordered aggregates. Nanoparticles also suppress lipid phase separation, in a concentration-dependent fashion. A general, yet simple thermodynamic model is developed to show that the change of lipid–lipid enthalpy is the dominant driving force towards the nanoparticle-induced destabilization of phase separation.